A dimensão social da política de acesso à justiça efetiva: Juizado Especial Cível como vetor de desenvolvimento nas comarcas de entrância intermediária do Estado do Maranhão - COELHO, Lavínia Helena Macedo (2019)
This dissertation analyzes the judicial administrative political effects that the Civil Special Court adopted as a vector of development by disseminating rights and ensuring the right place to plead them, based on the lessons of Professor Amartya. He is considered a watershed, after the constitutional reforms of the Judiciary, the Special Civil Court also established ground for the implementation of neoliberalism, but the distribution of justice for the most vulnerable, its main objective, was contested. Starting from the dichotomy between being an instrument of legal security for social and economic relations or a welfare mechanism, to contain the clamors of capitalism, judicial policy is evaluated, which prioritized its implementation from the perspective of legal and jurisdictional operators, in order to verify capable of guaranteeing effective and quality judicial protection, which, in addition to those who are deprived of a lower income, empowers the local population, historically excluded from the Justice System.